2006
DOI: 10.1042/bj20051253
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein isoform 2A expression is inducible and protects against ROS-mediated cell death in rotenone-treated HeLa cells

Abstract: The role of MT (metallothionein) gene expression was investigated in rotenone-treated HeLa cells to induce a deficiency of NADH:ubiquinone oxidoreductase (complex I). Complex I deficiency leads to a diversity of cellular consequences, including production of ROS (reactive oxygen species) and apoptosis. HeLa cells were titrated with rotenone, resulting in dose-dependent decrease in complex I activity and elevated ROS production at activities lower than 33%. Expression of MT2A (MT isoform 2A), but not MT1A or MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Nonetheless, the results of the in vitro experiments are in accordance with the results of the epidemiological studies conducted on Taiwan population, showing an enhanced incidence of OSCC development in patients with simultaneous areca quid and cigarette consumption (Ko et al, 1995, Lin et al, 2011. Moreover, this results also underlie the results of studies showing upregulated expression in response to reactive oxygen species (Iqbal et al, 2003;Reinecke et al, 2006). As areca nuts contain also high amounts of copper ions, high MT-1/2 expression in OSCC originating from areca nut chewers may be partially explained by its interaction with this metal ion.…”
Section: Areca Nuts Copper Ions and Reactive Oxygen Species (Ros)supporting
confidence: 80%
“…Nonetheless, the results of the in vitro experiments are in accordance with the results of the epidemiological studies conducted on Taiwan population, showing an enhanced incidence of OSCC development in patients with simultaneous areca quid and cigarette consumption (Ko et al, 1995, Lin et al, 2011. Moreover, this results also underlie the results of studies showing upregulated expression in response to reactive oxygen species (Iqbal et al, 2003;Reinecke et al, 2006). As areca nuts contain also high amounts of copper ions, high MT-1/2 expression in OSCC originating from areca nut chewers may be partially explained by its interaction with this metal ion.…”
Section: Areca Nuts Copper Ions and Reactive Oxygen Species (Ros)supporting
confidence: 80%
“…However, oxidative stress, a condition characterized by the dramatic increase in ROS levels and the disruption of the antioxidant balance, results in oxidative damage to cellular structures, signal transduction changes and cell death [13] . In addition, many studies have reported that ROS induce apoptosis in various cancer cells [14][15][16] . The mitochondrial membrane potential and the expression of Bcl-2 family proteins, which have been closely linked to mitochondrial-mediated apoptosis, were also reported to be affected by ROS [17] .…”
Section: Introductionmentioning
confidence: 99%
“…For MT2A, this may be due to the relatively high level of basal expression of the gene (Ref. 29 and data not shown). In addition, studies have shown that RNAPII can be localized to promoters of low expressing genes prior to gene activation, and these genes are poised for activation by environmental cues (30 -34).…”
Section: Discussionmentioning
confidence: 99%